Zerumbone alleviates neuropathic pain through the involvement of L-arginine-nitric oxide-cGMP-K+ ATP channel pathways in chronic constriction injury in mice model - Zulazmi, Nurul Atiqah; Gopalsamy, Banulata; Chia, Jasmine Siew Min; Farouk, Ahmad Akira Omar; Sulaiman, Mohd Roslan; Bharatham, B. Hemabarathy; Perimal, Enoch Kumar (MDPI, 2017)
The present study investigates the involvement of the l-arginine-Nitric Oxide-cGMP-K⁺ ATP pathways responsible for the action of anti-allodynic and antihyperalgesic activities of zerumbone in chronic constriction injury (CCI) induced neuropathic pain in mice. The role of l-arginine-NO-cGMP-K⁺ was assessed by the von Frey and the Randall-Selitto tests. Both allodynia and hyperalgesia assessments were carried out on the 14th day post CCI, 30 min after treatments were given for each respective pathway. Anti-allodynic and antihyperalgesic effects of zerumbone (10 mg/kg, i.p) were significantly reversed by the pre-treatment of l-arginine (10 mg/kg), 1H [1,2,4]Oxadiazole[4,3a]quinoxalin-1-one (ODQ), a soluble guanosyl cyclase blocker (2 mg/kg i.p.) and glibenclamide (ATP-sensitive potassium channel blocker) (10 mg/kg i.p.) (p < 0.05). Taken together, these results indicate that systemic administration of zerumbone produces significant anti-allodynic and antihyperalgesic activities in neuropathic pain in mice possibly due to involvement of the l-arginine-NO-cGMP-PKG-K⁺ ATP channel pathways in CCI model.